Nomenklatur Baru Pendidikan Islam di Era Industrialisasi - Masdar Hilmy (Universitas Darussalam Gontor, 2012)
The coming of industrialization era is irreversible, albeit the rejection by some. Among Muslims, industrialization is responded differently; some welcome while some others reject uncritically the logics behind the industrialization process. Whether like ordislike, sooner or later, Muslims in the end must live by industrialization era. What the Muslims need in response to the coming of industrialization era is to formulate a workable blue-print with which Muslims feel comfortable as an epistemological foundation of the Muslim faith. Such a blue-print is expected to be able to cope with the ontological, epistemological and axiological problems created by existing industrialization process.Industrialization process, in my argument, should have not deprived the existential being of the Muslim society. The fact is that the industrialization projects result in the dehumanizing people. A proper industrialization must place people as the subject, not the object, of the entire process of industrialization. Far from an ambition to present a complete solution to the current crises faced by Muslims, the need to formulate a new blue-print of industrialization-based Islamic education will be elaborated by this paper.